2008
DOI: 10.1182/blood-2007-04-084293
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in CCG-2961, a Children's Oncology Group Phase 3 Trial for untreated pediatric acute myeloid leukemia: a report from the Children's Oncology Group

Abstract: CCG-2961 incorporated 3 new agents, idarubicin, fludarabine and interleukin-2, into a phase 3 AML trial using intensivetiming remission induction/consolidation and related donor marrow transplantation or high-dose cytarabine intensification. Among 901 patients under age 21 years, 5-year survival was 52%, and event-free survival was 42%. Survival improved from 44% between 1996 and 1998 to 58% between 2000 and 2002 (P ‫؍‬ .005), and treatment-related mortality declined from 19% to 12% (P ‫؍‬ .025). Partial repla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
233
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(250 citation statements)
references
References 57 publications
14
233
0
3
Order By: Relevance
“…18 Furthermore, a recently published study conducted by the same group, CCG 2961, again demonstrated significantly better diseasefree survival for children with AML receiving related donor HSCT in CR1, vs chemotherapy only (60 vs 50%; P ¼ 0.02). 19 In our study, the 3-year TRM was 11% in our CR1 HSCT recipients. This relatively low TRM could be explained by the fact that most of our CR1 patients received matched related donor cells and had better organ function and less infectious complications compared with CR2 patients.…”
Section: Discussionmentioning
confidence: 46%
“…18 Furthermore, a recently published study conducted by the same group, CCG 2961, again demonstrated significantly better diseasefree survival for children with AML receiving related donor HSCT in CR1, vs chemotherapy only (60 vs 50%; P ¼ 0.02). 19 In our study, the 3-year TRM was 11% in our CR1 HSCT recipients. This relatively low TRM could be explained by the fact that most of our CR1 patients received matched related donor cells and had better organ function and less infectious complications compared with CR2 patients.…”
Section: Discussionmentioning
confidence: 46%
“…En cuanto a los resultados clínicos, las conclusiones de esta evaluación serían válidas incluso con un esquema diferente al BFM, pues la razón por la que no hay consenso sobre cuál de los protocolos de quimioterapia debe emplearse es, precisamente, que en los ensayos clínicos aleatorios no se reporta superioridad significativa de ninguno frente a los demás en términos de la supervivencia libre de enfermedad o en la global (25,28,29). El principal elemento diferenciador de los esquemas de quimioterapia es su costo, factor que quedó cubierto con el análisis de sensibilidad, lo que permitió concluir que la razón de costoefectividad del trasplante no era sensible al costo de la quimioterapia, por lo que los resultados se mantendrían para cualquiera de los esquemas de quimioterapia actualmente empleados en la consolidación de la leucemia mieloide aguda.…”
Section: Discussionunclassified
“…Moreover, recently presented results of CALGB trial 19808 in which patients under age 60 with untreated AML were randomized to receive IL-2 or observation after intensive post-remission therapy suggested a trend for a threeyear disease-free (56% 'v' 45%, P 5 0.11) and overall (68% 'v' 61%, P 5 0.09) survival benefit for those randomized to immunotherapy [49]. Although these studies suggest that post-remission immunotherapy could have a role in younger AML patients, randomized trials of IL-2 in the post-autograft setting in adults [50] and post-chemotherapy setting in children [51] each failed to demonstrate superiority of the experimental arm.…”
Section: Discussionmentioning
confidence: 99%